Praxisbuch Ethik in der Notfallmedizin Orientierungshilfen für kritische Entscheidungen - Salomon, Fred (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2015)
The work presents ethical challenges and decision-making conflicts from the wide field of internal and extra-clinical emergency medicine and provides practical decision-making aids through food for thought and ethical arguments. It is aimed at doctors and nurses from different disciplines, across multiple disciplines and professions, emergency services employees from various organizations and institutions, managers and sponsors of clinics and emergency services, employees of crisis intervention teams, and ethics advisors and ethics committees.